2009
DOI: 10.1016/j.jviromet.2008.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four nasal sampling methods for the detection of viral pathogens by RT-PCR—A GA2LEN project

Abstract: The aim of this study was to compare the efficacy and patient discomfort between four techniques for obtaining nasal secretions. Nasal secretions from 58 patients with symptoms of a common cold, from three clinical centers (Amsterdam, Lodz, Oslo), were obtained by four different methods: swab, aspirate, brush, and wash. In each patient all four sampling procedures were performed and patient discomfort was evaluated by a visual discomfort scale (scale 1-5) after each procedure. Single pathogen RT-PCRs for Rhino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 37 publications
1
44
0
Order By: Relevance
“…These findings expand on those of previous studies of nasal sampling in children (1,4,5,8,10) and have implications for the diagnosis and study of respiratory viruses. First, nasal selfsampling was simple, was preferred to staff collection, and may enable testing of more people earlier in the course of their illnesses.…”
supporting
confidence: 80%
“…These findings expand on those of previous studies of nasal sampling in children (1,4,5,8,10) and have implications for the diagnosis and study of respiratory viruses. First, nasal selfsampling was simple, was preferred to staff collection, and may enable testing of more people earlier in the course of their illnesses.…”
supporting
confidence: 80%
“…• Nasal swab Although a nasopharyngeal aspirate (NPA) is considered to be the best specimen for detecting influenza A viruses, [53][54][55] this procedure causes more discomfort and is more difficult to perform, particularly in children. Indeed, studies attempting to collect daily NPA samples from subjects have reported problems with subjects' tolerance and compliance with the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 Reverse transcription of RNA material isolated from nasopharyngeal samples was performed as described previously [12]. RNA was extracted from 50μl of nasal aspirates using Trizol reagent (Invitrogen, CA, USA).…”
Section: Influenza Virological Diagnosismentioning
confidence: 99%
“…Four microliters of cDNA were used in the first round PCR reaction mix, while 2μl of the PCR product of the first round were used in the amplification mixture of the second round [14]. Samples were amplified in a PTC-200 DNA Engine thermocycler (MJ Research, MA, USA) with previously described thermocycling conditions [12].…”
Section: Influenza Virological Diagnosismentioning
confidence: 99%